2006
DOI: 10.1021/bc050335b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Grafting of Thioctic Acid−PEG−Folate Conjugates onto Au Nanoparticles for Selective Targeting of Folate Receptor-Positive Tumor Cells

Abstract: This paper reports the creation of Au nanoparticles (AuNP) that are soluble in aqueous solution over a broad range of pH and ionic strength values and that are capable of selective uptake by folate receptor positive (FR+) cancer cells. A novel poly(ethylene glycol) (PEG) construct with thioctic acid and folic acid coupled on opposite ends of the polymer chain was synthesized for targeting the AuNP to FR+ tumor cells via receptor-mediated endocytosis. These folic acid-PEG-thioctic acid conjugates were grafted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(173 citation statements)
references
References 36 publications
(36 reference statements)
3
163
1
1
Order By: Relevance
“…enzymes, receptors, antibodies, DNA) and cells, but they are also very attractive candidates for use as carriers in medical diagnosis and treatment. [7][8][9][10][11][12][13][14][15][16][17][18] Gold (Au) nanoparticles are well known for their surface plasmon resonance band (SPR), a phenomenon associated with coherent oscillations of conduction-band electrons on the nanoparticle surface upon interaction with light. 2,19 The wavelength of the SPR band depends from the chemical nature, size, shape and aggregation of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…enzymes, receptors, antibodies, DNA) and cells, but they are also very attractive candidates for use as carriers in medical diagnosis and treatment. [7][8][9][10][11][12][13][14][15][16][17][18] Gold (Au) nanoparticles are well known for their surface plasmon resonance band (SPR), a phenomenon associated with coherent oscillations of conduction-band electrons on the nanoparticle surface upon interaction with light. 2,19 The wavelength of the SPR band depends from the chemical nature, size, shape and aggregation of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include use of anti-FRα antibodies [10] or folic acid-conjugates to localize drugs [28][29][30], imaging compounds [31][32][33], T cells [34,35], nanoparticles [36], or oncolytic viruses [37] to FRα-expressing tumors. Besides these efforts, we have recently shown that FRα may have potential as a target for immunotherapeutic approaches in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[117] For cancer therapy, folic acid (FA) or methotrexate (MTX) can be anchored onto nanoparticles for recognition by folate receptors, which are overexpressed on surfaces of many cancer cells. FA-grafted gold nanoparticles [118] or iron oxide [119] nanoparticles are specifically uptake by folate receptor-positive KB cells. Methotrexate provides an additional advantage as it can serve as a targeting ligand as well as a chemotherapeutic drug.…”
Section: In Vivo Targeting Of Nanoparticlesmentioning
confidence: 99%